Floating Bilayered Tablets: A Novel Approach in Gastro-Retentive Drug Delivery System - Ishika Bijore; Vikrant Wankhede; Shrikant Pande; Abhishek Mankar; Saurabh Bodke; Shrirang Virkhare (Asian Journal of Pharmaceutical Research and Development, 2026)
Floating bilayered tablets represent an advanced gastro-retentive drug delivery approach designed to enhance the bioavailability of drugs that exhibit narrow absorption windows or poor solubility in alkaline environments. This review provides an in-depth overview of recent progress in the design, formulation, and evaluation of EFBTs. The effervescent mechanism relies on acid–base interactions, typically involving sodium bicarbonate and citric acid, which generate carbon dioxide to achieve rapid buoyancy and prolonged gastric residence. The bilayer configuration combines a floating or immediate-release layer with a sustained-release layer, ensuring controlled drug release and improved pharmacokinetic performance. Various studies have demonstrated floating lag times of less than one minute, sustained release over 12–24 hours, and marked enhancement in relative bioavailability and patient compliance. Drugs such as eplerenone, levofloxacin, nicotinamide, and clarithromycin have shown significant therapeutic benefits when formulated as FBTs. Key formulation aspects—including polymer selection, gas-generating agents, and matrix integrity—play vital roles in optimising drug release kinetics and buoyancy characteristics. Furthermore, the review discusses critical evaluation parameters, stability profiles, and regulatory considerations that influence the successful translation of laboratory findings into commercial dosage forms. Overall, effervescent floating bilayered tablets offer a versatile and patient-friendly platform for achieving sustained gastric retention, controlled release, and enhanced therapeutic efficacy in oral drug delivery.